Effectiveness of projectile screening in single and multiple ionization of Ne by B2+ - Wolff, W. (2011)
Pure multipleionization cross sections of Ne by B2+ projectiles have been measured in the energy range of 0.75 to 4.0 MeV and calculated using the continuum distorted wave eikonal initial state approximation. The experiment and calculations show that the ionization cross sections byB2+,principally for the production ofhighly charged recoils, is strongly enhanced when compared to the bare projectile with the same charge state, He2+, at the same elocities.